A Quasi-Direct Numerical Simulation of a Compressor Blade with Separation Bubbles and Inflow Turbulence - Guglielmo Vivarelli; João Anderson Isler; Chris D. Cantwell; Francesco Montomoli; Spencer J. Sherwin; Yuri Frey-Marioni; Marcus Meyer; Iftekhar Naqavi; Raul Vazquez-Diaz (International Journal of Turbomachinery, Propulsion and Power)
Within the turbomachinery industry, components are currently assessed deploying standard second-order steady solvers. These are unable to capture complicated unsteady phenomena that have a critical impact on component performance. In this work, the high-order spectral h/p solver Nektar++ will be applied to a compressor blade to study the turbulent transition mechanisms and assess the effect of incoming disturbances with quasi-DNS resolution. The case will be modelled at an angle of incidence of <semantics>53.5°</semantics> to match the original experimental loading at <semantics>52.8°</semantics>. At clean inflow conditions, Kelvin–Helmholtz instabilities appear on both sides of the blade due to a double separation, with the pressure side one not being reported in the experiments. The separation is gradually removed by the incoming turbulent structures but at different rates on the two sides of the blade. It will be shown that there is an optimal amount of turbulence intensity that minimises momentum thickness, which is strongly related to losses. Moreover, a discussion on the spanwise extrusion will be included, this being a major player in the modelling costs. Finally, the wall-clock time and the exact expenditure to run this case will be outlined, providing quantitative evidence of the feasibility of considering a quasi-DNS resolution in an industrial setting.